Innovation in Public Services Through the Independent Population Administration Kiosk (ADM) at the Department of Population and Civil Registration of Balikpapan City - Mayada Putri Nor Fadhila; Trenda Aktiva Oktariyanda (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Along with the rapid population growth in Indonesia and there are also findings of various maladministration problems in the implementation of population administration services in Indonesia, the government is encouraged to create a technology-based innovation. The Directorate General of Population and Civil Registration of the Ministry of Home Affairs created an innovation, namely in the form of the Independent Dukcapil Pavilion Machine (ADM). In this case, the public can print population documents independently on the ADM machine in a short time. The Balikpapan City Population and Civil Registration Office is one of the population agencies that organizes the innovation. This study uses a qualitative descriptive research method. The focus of the research uses the theory of innovation typology proposed by Halvorsen et al. 2005, namely a new or improved service, process innovation, administrative innovation, system innovation, conceptual innovation, radical change of rationality. According to Miles and Huberman, the data analysis techniques used are, data collection, data reduction, data display, conclution drawing/verification. The results of this study show that the implementation of the ADM machine in Dukcapil Balikpapan has been running well, many people use and feel helped by the existence of this ADM machine. However, not a few people still have difficulty accessing this ADM machine, so they need the help of Balikpapan Dukcapil officers.